Eficacia de varios insecticidas en el control del gusano blanco de la papa Premnotrypes vorax (Hust.) [Solanum tuberosum, Ecuador] - Merino, Gualberto; Vazquez, Víctor (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The potato white tubberworm Premnotrypes vorax (Hust) is the mmost serious pest of potato crop in Ecuador. Since 1958 control has been achieved with Aldrin and Dieldrin incorporated to the soil before planting but its no longer efficiency in areas frecuently treated, put the farmers in a discouraging situation. In 1975 and 1976 in two areas severely infested in Chimborazo province, four experiments were carried out on the chemical control of this insect pest.